Mejoramiento genético y actividades relacionadas. Mejoramiento de características individuales. Adaptación a temperatura-fotoperíodo - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Evaluation of photoperiod bean response in flowering screening continued at CIAT-Palmira, using artificial 18 h daylengths to delay flowering. Approx. 600 germplasm accessions were evaluated in 1986 as a part of continuing efforts to characterize responses of germplasm in different bean production regions. To introduce desirable characteristics into Phaseolus vulgaris, 70 accessions of 3 other Phaseolus species (P. acutifolius, P. coccineus, and P. lunatus) were also evaluated. P. acutifolius and P. coccineus were notable for their high levels of sensitivity. Results are included in table form. (CIAT)